Psychosocial predictors and justification patterns of traditional and alternative medicine in Peru - Angelo Fasce; Jose Rosales-Trabuco; Javier Rodriguez-Ferreiro; Itxaso Barberia; Elvis Pinedo-Yzaguirre; Juan Manuel Espinoza Nunez; Wilson Marcos Ortiz-Treviños; Christian David Pizarro-Moncada; Mario Reyes-Bossio; Carlos Carbajal-León; Ezequiel Lopez-Lopez (Humanities and Social Sciences Communications, 2026)
Abstract This mixed-methods study investigates the prevalence, attitudes, psychological predictors, and reasons for perceived effectiveness of traditional and alternative medicine in Peru. A representative national sample ( N = 805) reported their experiences with 16 unconventional medical techniques, alongside psychometric measures of pseudoscientific beliefs, ideological traditionalism, and trust in the medical profession. Traditional medicine was more widely used, while alternative medicine elicited more favorable attitudinal responses. Pseudoscientific beliefs predicted greater endorsement of both modalities, with traditionalism specifically linked to traditional medicine. To enrich the psychometric findings, we applied natural language processing techniques to 2716 reasons for perceived effectiveness extracted from spontaneous open-ended responses, revealing distinct rhetorical patterns: alternative medicine was more often justified through pseudoscientific and biomedical-sounding arguments, whereas traditional medicine drew on cultural, spiritual, and experiential narratives. Network and co-occurrence analyses confirmed that both modalities follow distinctive general combinatory logics of justification. However, subgroups mixing traditional and alternative medicine also emerged, such as spiritually oriented practices and techniques pivoting traditionalist conceptions. These findings reflect the interplay between global health discourses and local belief systems. Overall, this study highlights the value of integrating cultural and linguistic analyses to understand public engagement with unconventional health practices.